Investigation of two‐ and three‐bond carbon–hydrogen coupling constants in cinnamic acid based compounds. (29th June 2016) - Pierens, Gregory K.; Venkatachalam, Taracad K.; Reutens, David C.
Abstract: Two‐ and three‐bond coupling constants ( 2 J HC and 3 J HC ) were determined for a series of 12 substituted cinnamic acids using a selective 2D inphase/antiphase (IPAP)‐single quantum multiple bond correlation (HSQMBC) and 1D proton coupled 13 C NMR experiments. The coupling constants from two methods were compared and found to give very similar values. The results showed coupling constant values ranging from 1.7 to 9.7 Hz and 1.0 to 9.6 Hz for the IPAP‐HSQMBC and the direct 13 C NMR experiments, respectively. The experimental values of the coupling constants were compared with discrete density functional theory (DFT) calculated values and were found to be in good agreement for the 3 J HC . However, the DFT method under estimated the 2 J HC coupling constants. Knowing the limitations of the measurement and calculation of these multibond coupling constants will add confidence to the assignment of conformation or stereochemical aspects of complex molecules like natural products. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Two‐bond and three‐bond coupling constants were determined for a series of 12 substituted cinnamic acids using a selective 2D IPAP‐HSQMBC and 1D proton coupled 13 C NMR experiments. The experimental values of the coupling constants were compared with DFT calculated values and were found to be in good agreement for the 3 J HC coupling constants however underestimated the 2 J HC coupling constants.